EVALUATION OF ALTERED PTEN EXPRESSION BY IHC AS A DIAGNOSTIC MARKER IN HYPERPLASTIC AND NEOPLASTIC ENDOMETRIUM OBSERVATIONAL DESCRIPTIVE STUDY.: Altered PTEN expression by IHC in endometrial disorders - Behera, Bodhisatwa; Nayak, Jayanti; Mohanty, Saroj Ranjan; Patro, Manoj Kumar; Senapati, Sunita Rani; Dash, Neha (Student's Journal of Health Research Africa, 2023)
Introduction: Endometrial carcinoma is a common cancer affecting women. Different molecular alterations have been described in endometrioid endometrial carcinoma (EC). Among them the most frequently altered is the loss of the PTEN protein, a tumor suppressor gene, leading to microsatellite instability. The purpose of this study was to evaluate the expression pattern of PTEN gene in normal proliferative, hyperplastic, and neoplastic endometrium. Objective: To observe the altered expression of PTEN in proliferative endometrium, endometrial hyperplasia, and endometrial carcinoma. Methods: This study was an observational descriptive study conducted in the Department of Pathology, M.K.C.G. Medical College, Brahmpur,Odhisha. over a two-year period in which immuno-histochemical evaluation of PTEN expression was done in 146 patients. Results: PTEN immunoreactivity was present in all normal proliferative endometrium, all simple hyperplasia, 50% of atypical hyperplasia, and in none of EC (P < 0.001). The intensity of PTEN reaction was significantly higher in a group with proliferative endometrium than in atypical hyperplastic endometrium and EC (P < 0.001). Conclusion: PTEN expression was significantly higher in cyclical endometrium than in atypical hyperplasia and endometrioid carcinoma and PTEN immunostaining may be a new and effective tool for screening malignant and premalignant endometrial lesions